Effect of low level laser therapy on revascularization of free gingival graft using ultrasound Doppler flowmetry - Lalitha T. Arunachalam; Uma Sudhakar; Akila Sivaranjani Janarthanam; Nimisha Mithra Das (Journal of Indian Society of Periodontology, 2014)
Low level laser therapy (LLLT) is widely used during the post-operative period to accelerate the healing process. It promotes beneficial biological action on neovascularization with anti-inflammatory and analgesic effects. Two systemically healthy patients with Miller′s grade II recession on 33 and 41, respectively, were treated with free gingival graft. After surgery, second patient received LLLT using a 830 nm diode laser, with output power of 0.1 W on the first day half hour following surgery, on the third day, seventh day, and lastly on the ninth day. Both the patients were asked to assess the pain on second, fourth and tenth day using a Numerical Rating Scale and revascularization of the grafted area was assessed using a color Doppler ultrasound imaging on the fourth and the ninth day. Neovascularization was noted in both the patients but the second patient elicited marked increase in vascularity on the fourth as well as the tenth day and drastic reduction in pain on day four, with no change on the tenth day. The results showed that LLLT was an effective adjunctive treatment in promoting reevascularization and pain control during early healing of free gingival graft.